Unveiling the determinants of femicide in Ecuador: a comprehensive analysis - Juan Pablo Díaz-Sánchez; Cintya Lanchimba; Diego Albuja; Yulissa Ramírez (Frontiers in Sociology)
This paper reports an investigation of the determinants of femicide using the context of Ecuador as case of study. To do so, we use official data spanning 2018 to 2022 from the National Survey on Family Relations and Gender Violence against Women in Ecuador with a dataset revealing 1,325 femicides and violent deaths of cisgender women and girls. Using a probit regression model, we find that several variables related to perpetrators’ such as level of education, employment status, and variables related to the crime itself such as location emerge as pivotal factors in understanding femicide incidents. This study contributes to a more profound comprehension of femicide’s multifaceted determinants, emphasizing the dynamic nature of these factors. The research aids in the development of evidence-based policies to address this societal issue effectively.